From citrus peel to the classroom: Kitchen microbiology worksheet to improve prospective science teachers’ concept understanding and hands-on skills - Fibriana, Fidia; Wiyanto, Wiyanto; Widiyatmoko, Arif; Heriyanti, Andhina Putri; Nurazizah, Kaylha Salsabilla; Syah, Ahmad Firman (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2025)
Understanding the concept and hands-on skills in microbiology is crucial for science teachers because they help students develop critical thinking and retain information. This study aimed to develop a team-based project worksheet using a kitchen microbiology approach to improve students’ concept understanding and hands-on skills in identifying fungi from orange peels (Citrus spp.). The research employed a modified Borg and Gall R&D method to develop the worksheet (planning, product development, limited trials, and product revision). A limited trial was conducted to assess the students’ performance in a small-scale study involving 9 students selected from the Science Education Undergraduate Study Program at Universitas Negeri Semarang, using a one-group pretest-posttest design. The worksheet was validated, and all data were analyzed quantitatively. The results of worksheet validation by media and content experts indicated the worksheet is highly feasible (average >93%). Results showed a significant improvement in concept understanding and hands-on skills, with an N-Gain of 0.71. In conclusion, the kitchen microbiology-based worksheet effectively enhanced students’ concept understanding and hands-on skills while requiring further refinement. Its novelty lies in the use of everyday kitchen materials as educational media, the integration of teamwork and scientific communication, and the interdisciplinary blend of microbiology and sustainability, positioning it as a promising contextual learning model with both practical and social impact.